Standard handbook of architectural engineering : a practical manual for architects, engineers, contractors and related professions and occupations - Butler, Robert Brown (New York : McGraw-Hill, 1998)
Introduction; design; Structure; Climate; Plumbing; Electrical; Illumination; Acoustics.
Includes bibliographical references and index.
Keywords: Building; Building -- Handbooks, manuals, etc